Exploring Strategic Management and Co-Creation in the World: A Bibliometric Review from Scopus Database Journal - Heryani, Yani; Triansyah, Fadli Agus; Wibowo, Lili Adi; Junia, Annisa Aghniarahma; Lizein, Baandaalr; Inomjon, Qudratov (Universitas Negeri Malang, 2024)
In the contemporary age of globalization, business and industry are experiencing dynamic and rapid changes. Strategic management and co-creation are a critical approach to management that combines business strategy with active stakeholder collaboration to create added value and competitive advantage. This study investigates developments in the literature related to the topic